Pendidikan Karakter Islami Melalui Pembelajaran PAI di Sekolah Kejuruan - Yasin Nurfalah; Ahid, Nur (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Character education in Indonesia, especially in the context of Islamic religious education (PAI), is becoming an increasingly pressing issue with the emergence of various immoral cases among students. This study aims to explore how PAI can play a role in shaping the Islamic character of students in Vocational High Schools (SMK), with a focus on gender dynamics at SMKN 1 and SMKN 2 Kediri City. This study uses a qualitative approach with a multi-site study design involving two vocational schools, aiming to explore how PAI education can contribute to the formation of gender-based student character. In this context, the importance of inclusive character education that is responsive to students' needs is the main focus. This discussion provides a clearer picture of the problems of Islamic education, especially in the formation of Islamic character through PAI learning in vocational schools. It is hoped that these findings can be the basis for further development in character education in Indonesia.